The social relations that construct quality of life of older people living in long-term care government facilities in Tshwane district : an institutional ethnography enquiry - Hlongwane, Mikateko Nomvula Naomi (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.